Does High-Speed Rail Opening Affect the Health Care Environment?–Evidence From China - Song, Cai-Xia; Qiao, Cui-Xia; Luo, Jing (Frontiers in Public Health, 2021)
Using the panel data of 280 prefecture-level cities in China from 2004 to 2014, this paper examines the effects of high-speed rail opening on health care environment based on Difference-in-Differences method (DID). Through an empirical analysis, the results proved that high-speed rail opening can significantly promote the health care environment and this effect is different in regions with different levels of economic development. Finally, we tested the mechanisms of how the high-speed rail opening affects the healthcare environment. High-speed rail opening improves the healthcare environment by increasing road accessibility and promoting economic development. Our results support the view that high-speed rail opening has an important contribution to the improvement of health care conditions.